Pemetaan Particulate Matter 10 di Bundaran Taman Pelangi Kota Surabaya - Zakaria Amrizal; Ida Munfarida; Amrullah (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2021)
Air pollution is an annual problem that occur in every city. Surabaya is one of the cities with a fairly dense population so it is directly proportional to the number of motor vehicles used. Motor vehicles and industrial areas were located in Surabaya contribute the largest emissions to the air so they have low air quality because of the pollution. Air quality is closley associated with pollution, to ascertain the levels of contamination are calculated in reference to the Standard Index of Air Pollution. One of the monitoring parameters used is Particulate matter 10. PM10 is a primary pollutant that emits directly into the air which has serious impacts on health and the environment. This research was conducted in Traffic Ring Taman Pelangi Surabaya for 3 days with an interval of weekdays and holidays with time intervals in the morning, afternoon and evening. Analysis of concentration data was calculated using the HVAS tool with the gravimetric method and mapped using the ArcGIS program. The results of the study showed that the highest concentration was at the sampling location point 6 with a value of PM10 = 110.71 μg/m3, and the lowest was at the sampling location point 1 with a value of PM10 = 50.15 μg/m3